Pelatihan Santripreneur Melalui Pengenalan Digital Marketing Untuk Santri Pondok Pesantren Darul Ulum Tragung Batang - Fuadi, Ariza; Kurnia, Akhmad Syakir; Firmansyah; Sugiyanto, FX; Zusak, M Bastomi Fahri (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
This Community Service Program aims to empower students of the Darul Ulum Tragung Islamic Boarding School, Batang, through digital marketing training to develop their ultra-micro businesses. This training was conducted in three stages: introduction to digital marketing, case studies from other Islamic boarding schools, and creation and management of a marketplace. The results of the training showed an increase in students' understanding of digital marketing strategies and their ability to manage a marketplace. Several obstacles such as limited internet access and devices, as well as limited time in the Islamic boarding school environment, were successfully overcome with an adaptive approach. This program succeeded in providing strong digital-based entrepreneurial provisions for students while strengthening partnerships between Islamic boarding schools and universities.